Phenylketonuria Diet Promotes Shifts in Firmicutes Populations - Bassanini, Giulia; Ceccarani, Camilla; Borgo, Francesca; Severgnini, Marco; Rovelli, Valentina; Morace, Giulia; Verduci, Elvira; Borghi, Elisa (Frontiers in cellular and infection microbiology, 2019)
Low-phenylalanine diet, the mainstay of treatment for phenylketonuria (PKU), has been shown to increase glycemic index and glycemic load, affecting the availability of substrates for microbial fermentation. Indeed, changes in the PKU gut microbiota compared with healthy controls have been previously reported. In this study we compared the gut microbial communities of children with PKU and with mild hyperphenylalaninemia (MHP, unrestricted diet). For each group, we enrolled 21 children (4-18 years old), for a total dataset of 42 subjects. We assessed dietary intake and performed gut microbiota analysis by sequencing the V3-V4 hypervariable regions of the 16S rRNA gene. Short chain fatty acids (SCFAs) were quantified by gas chromatographic analysis. While alpha-diversity analysis showed no significant differences between PKU and MHP groups, microbial community analysis highlighted a significant separation of the gut microbiota according to both unweighted ( = 0.008) and weighted Unifrac distances ( = 0.033). Major differences were seen within the Firmicutes phylum. Indeed, PKU children were depleted in spp. and enriched in spp. and spp (family ). We found a divergent response of members of the Firmicutes phylum with respect to daily glycemic index, higher in PKU children. , unclassified and, to a lesser extent spp. negatively correlated with glycemic index, whereas unclassified were positively associated. Indicator species analysis suggested be related to MHP status and to be associated with PKU. Despite PKU children having a higher vegetable and fiber intake, resembling a vegan diet, their gut microbial profile is different from the microbiota reported in the literature for individuals consuming a high-fiber/low-protein diet. Indeed, beneficial microorganisms, such as , considered a biomarker for a healthy status and one of the main butyrate producers, are depleted in PKU gut microbiota. We suggest that both the quality and quantity of carbohydrates ingested participate in determining the observed Firmicutes shifts on the PKU population.